Daniel Cunha, Solitude: Piano Works by Alfredo Napoleão (CD Decurio, 2018) - Ferreira, João Costa (Revista Portuguesa de Musicologia, 2020)
Recensão: Daniel Cunha, Solitude: Piano Works by Alfredo Napoleão (CD Decurio, 2018)